Strategies of Narrative Coherence: how Militias Justify Embracing State Power - Weil, Ari (Perspectives on terrorism, 2022)
What happens to the anti-government movement when someone they support takes power? When Donald Trump was elected in 2016, the U.S. militia movement faced a challenge of narrative coherence: the risk that the stories the movement tells were no longer logically consistent. This article investigates the Oath Keepers, a group that pivoted from staunch opposition to federal power to supporting Trump, and ultimately in 2020 called for massive military action to suppress protests and re-run the election. Through an analysis of 137 official Oath Keepers online statements and posts from 2015—2021 and over 4,000 comments by followers and members on those posts, two narrative strategies are identified. First, the group extended their existing narrative by continuing to tell Revolutionary War metaphors but made Trump the new protagonist in those stories. Second, they used semantic adjustments to avoid hypocrisy as they embraced central state power. As they aligned with Trump, the military gradually supplanted the militia as a key actor in their narratives of change. Additionally, in 2020 they told their followers to no longer use the term martial law in order to make their new narrative fit within their founding ideology. This article bridges work on narratives in terrorism studies and the large civil war literature on shifting alignments and provides a deeper understanding of the strategic messaging of anti-government extremists. At a more micro-level, the analysis of debates among followers gives insight into how anti-government extremists think about their relationship to the state.